Peran Penyuluh Pertanian dalam Penerapan Teknologi Alat dan Mesin Pertanian di Kelurahan Bangkal Kecamatan Cempaka Kota Banjarbaru - Refky Refdani; Usamah Hanafie; Abdussamad Abdussamad (AGRIDES: Jurnal Agribisnis Perdesaan, 2015)
Agricultural development has experienced a rapid shift from traditional to modemagriculture. Some important factors are considered to develop modem agriculture, include improvements oteccess to markets and advanced technology, economic stability, and government intervention. The research identifies the role of agricultural extension and the problems in agricultural machinery app/Jcationin Desa Bangkal, Kecamatan Cempaka, HanJarbaru. I he study finds that the education role is high, which mean that the extension can facilitate the learning process to meet farmer satisfaction .. The role of dissemination, facilitation, and consultation are also cc;3tegonzed as high. On the other hand, the role of supervision, monitoring and evaluation are categorized as medium. Thus, this problem should be tackled downto optimize the extension role.